MORPHOLOGY OF A SACRED URBAN LANDSCAPE: THE CASE STUDY OF SYLHET CITY, BANGLADESH - Saha, Kawshik; Sobhan, Rezwan; Nahyan, Mohammad (Journal of Architectural Research and Education, 2020)
This study investigates how different religious streams influence the morphological development of a historic city by giving a unique identity as a sacred landscape. Sylhet city, which is popularly known as the spiritual capital of Bangladesh, has been shaped by two different spiritual streams over years. From thousand years Sylhet is known for a transitional hub of political, cultural, ethnical and religious migration which shaped a unique urban fabric in the morphology of this city. The spirituality of Sylhet deeply influenced by two major streams of religious philosophy of both Islam and Hinduism, not in conventional form but in form or Sufism and Vaishnavism which is deeply rooted in a spirit of mysticism, humanity, and self-consciousness. God is prayed here not in form of temples or mosques but in Akhadas (informal shrine) and Mazars (tomb of saints, places are a mediator between creator and creation. These ritual centers also turned to be the focal point of the city surrounded by public spaces, road networks, commercial centers through the juxtaposition of sacred space and community space. Truly Mazars and Akhadas are a center of cultural transition beyond language, geography and race to shape this sacred land a spiritual identity and symbol of faith. This study focuses on these paradigms in terms of architecture and urban design to make a new approach to redefine the understanding of Sylhet city for future researchers and historians.